HUMAN CAPITAL: A DETERMINANT OF REGIONAL DEVELOPMENT? AN EMPIRICAL STUDY ON THE EUROPEAN UNION - OLIMPIA NEAGU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
The paper aims to investigate if human capital is a determinant of regional development accross EU countries. We used a regression model to show that economic growth in the EU countries is influenced by the tertiary educational level of population. Data from EUROSTAT, as tertiary educational attainement of population and GDP per capita in PPS at regional level (NUTS 2), over the period of 2002-2011, were used. We found a moderate validated statistical dependence between the variance of GDP per inhabitant and that of tertiary educational attainment of population accross European regions and a stronger link between them when we used time series of data.